A memoir of the young UP School of Economics - Sicat, Gerardo P. (Philippine Review of Economics, 2017)
The author recounts the intersection of his own career with the early years of development of the UP School of Economics. When that career in the School was interrupted by government service, his unique position in the national government enabled him to further participate in the development and growth of the School from the perspective of a major consumer of the supply of economists that the institution provides.